Characterization of patients with IgA nephropathy with and without associated minimal change disease - Guo, Wei-yi; Sun, Li-jun; Dong, Hong-rui; Wang, Guo-qin; Xu, Xiao-yi; Cheng, Wen-rong; Zhao, Zhi-rui; Ye, Nan; Liu, Yun; Cheng, Hong (Frontiers in Nephrology, 2023)
Introduction: IgA nephropathy (IgAN) display considerable heterogeneity in clinical manifestations and pathological phenotypes. Approximately 5% patients with IgAN presented with onset nephrotic syndrome, mild masangial lesions and diffuse foot process effacement resembling minimal change disease (MCD-IgAN). Nowadays, whether MCD-IgAN is a special type of IgAN or MCD accompany by IgA deposition remains controversy. Methods: 51 patients diagnosed as MCD-IgAN at Beijing Anzhen Hospital from January 2010 to September 2022 were recruited. We analyzed the clinical and pathological characteristics of IgA-MCD. IgAN without MCD (non-MCD-IgAN) and healthy control were enrolled as controls. Galactose-deficient IgA1 (Gd-IgA1) and complement C3 both in circulation and renal tissues were detected. Results: We found that the levels of serum Gd-IgA1 were lower in MCD-IgAN than non-MCD-IgAN, but higher than healthy controls. Gd-IgA1 barely deposited in glomeruli of MCD-IgAN, the positive rate was only 13.7% (7/51), while 82.4% (42/51) in non-MCD-IgAN. Among those renal Gd-IgA1 positive patients, Gd-IgA1 and IgA colocalized along the glomerular mesangial and capillary areas. Interestingly, we found the levels of circulation complement C3 in MCD-IgAN were significantly higher than in non-MCD-IgAN. Besides, the intensity of C3c in glomeruli in MCD-IgAN was significantly weaker than non-MCD-IgAN. Conclusions: our study suggested that in MCD-IgAN, most IgA that deposited on glomeruli was not the same pathogenic Gd-IgA1 as in general IgAN. The complement activation in both systemic circulation or in situ in MCD-IgAN were much weaker than in non-MCD-IgAN. Our study suggested that IgAN with MCD might be MCD with coincidental IgA deposition.